Legal problems of agricultural cooperation development in the conditions of digitalization in the Republic of Kazakhstan - Yerkinbayeva, L.; Kalymbek, B.; Nesipbayeva, I. (Bulletin of the Karaganda University “Law Series”, 2021)
This article examines some theoretical and practical issues of legal regulation of agricultural cooperative activities in the context of digitalization in Kazakhstan. Digitalization of the agricultural sector provides opportunities to improve the efficiency of agricultural cooperation, the study of legal problems of which will allow to effectively solve the problems of food security and rational use of agricultural land. The authors focus on the relevance of the problem under study, determine the place and role of digitalization in solving issues of agricultural cooperation. A comparative analysis of the legislation of foreign countries and the Republic of Kazakhstan in the field of agricultural cooperation and digitalization of agricultural entrepreneurship showed the lack of a unified concept for the implementation of digitalization of this area, which requires comprehension and legal support, including such areas as the creation of technologies that simplify the process of monitoring the use and protection of land of agricultural cooperatives; lending, subsidizing and insurance of agricultural cooperatives; the introduction of digital tools for the use of information resources, platforms and technologies that increase the efficiency of its activities; the implementation of digital platforms for monitoring and managing transport and logistics infrastructure in agriculture. It is proposed to legislate the goals and objectives of the digital transformation of the sphere of agricultural entrepreneurship in general, and to provide for measures to protect the rights and legitimate interests of agricultural entrepreneurs.